Programa tutorial en la mejora de manejo de conflictos en directivos de las instituciones educativas rurales, Muyuy, Fernando Lores, 2019 - Gomez Villacrez, Beatriz (2021)
The research was carried out in the rural area of Muyuy, and its main objective was to evaluate the effect of the application of the tutorial program in the improvement of conflict management in directors of rural Educational Institutions in the district of Fernando Lores. The type of research considered was the evaluative with longitudinal, field, and experimental design with a single group, with pre-test and post-test. The population was 16 managers, and the sample was for convenience. An instrument was available for data collection, which was validated by expert judgment and its reliability was determined through a pilot test. The results show that the prevention, negotiation, and mediation dimensions of the conflict transformation improved substantially after the application of the tutorial program; giving as a final conclusion that the application of the tutorial program significantly improves conflict management in managers of rural educational institutions in Muyuy because p-value = 0.000 <? / 2 = 0.025, with which the general hypothesis of the research is verified.